2019
DOI: 10.1002/admi.201901246
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Independent and Interdependent Role of Water and Oxidation on the Tribology of Ultrathin Molybdenum Disulfide (MoS2)

Abstract: In this work, the tribological behavior of ultrathin-MoS2 was investigated to understand the independent roles of water and oxidation. Water adsorption was identified as the primary interfacial mechanism for both SiO2/pristine-MoS2 and SiO2/graphene interfaces, however, tribological behavior of pristine-MoS2 was observed to be more sensitive to presence of water due to stronger MoS2-water interaction.Comparison of pristine-MoS2 and oxidized-MoS2 revealed that the oxidation of MoS2 significantly increased its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 57 publications
5
30
1
Order By: Relevance
“…The average coefficient of friction as a function of temperature for the steady-state friction cycles (cycles 100-1024) is shown in Figure 2a. For the tests in air, the friction is found to decrease with respect to temperature until 110 • C and begin to increase again at 120 • C. This effect is characteristic of MoS 2 tribological contacts at elevated temperatures when ambient humidity is present [28,29]; the ambient humidity allows water intercalation between 2D MoS 2 sheets [30,31] which hinders the van der Waals sliding and increases the interfacial shear strength. As temperature increases, the desorption of water from the contact increases and the MoS 2 has reduced resistance to shear.…”
Section: Friction Behaviourmentioning
confidence: 87%
“…The average coefficient of friction as a function of temperature for the steady-state friction cycles (cycles 100-1024) is shown in Figure 2a. For the tests in air, the friction is found to decrease with respect to temperature until 110 • C and begin to increase again at 120 • C. This effect is characteristic of MoS 2 tribological contacts at elevated temperatures when ambient humidity is present [28,29]; the ambient humidity allows water intercalation between 2D MoS 2 sheets [30,31] which hinders the van der Waals sliding and increases the interfacial shear strength. As temperature increases, the desorption of water from the contact increases and the MoS 2 has reduced resistance to shear.…”
Section: Friction Behaviourmentioning
confidence: 87%
“…This is not likely a concern when comparing to simulation results, as wear during the first few cycles of sliding has been shown to remove the oxidized surface film, eventually leading to a recovery of low friction by the formation of ordered films and transfer films on the countersurface [45,63]. This behavior is different from edges terminated by sulfur atoms, as oxides are also more likely to attract environmental contaminants like water [24,25,40].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between water molecules and unterminated edges of MoS 2 lamellae have also been suggested as an impediment to low-strength shear [33]. In macroscale contacts, edges of MoS 2 lamellae at the surface are likely oxidized prior to testing, further enhancing interactions with water [15,24,[38][39][40]. Previous work by our group showed that the surface microstructure (i.e., crystallite or lamellae size and thickness of the oriented layer) has a significant impact on friction behavior and its evolution in the presence of various vapor species, including water and molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Within the interfacial region, the hydrogen bonding network tends to form dynamically and further glues the surroundings together, which will renormalize the local interfacial interaction and further mediate the entire mechanical performance. [15][16][17][18] As one of carbon-based engineering structures, carbon bers with ultrahigh surface-to-volume ratios are usually bundled together to reinforce other materials. 19,20 The entire mechanical performance is mainly restricted by the interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%